Prospective observational study of blood pressure variation and malnutrition using body composition monitor in hemodialysis patient in tertiary care hospital - Hussain, Shuaib; George, Blessy K.; Ramaiah, Balakeswa (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Blood pressure (BP) variations and malnutrition are critical concerns in hemodialysis patients, significantly impacting morbidity, mortality and quality of life. Accurate assessments using tools such as the Body Composition Monitor (BCM) can guide effective interventions to improve outcomes. This study aimed to evaluate BP variations and malnutrition in hemodialysis patients using BCM, analysed dialysis-related complications and assess the impact of targeted interventions on patient outcomes. Methods: A prospective observational study was conducted on 125 hemodialysis patients at a tertiary care hospital. Data on BP variations, nutritional status and complications were collected using BCM and the Medical Outcomes Study Short Form-36 (MOS SF-36) questionnaire. Pharmacological and non-pharmacological interventions were tailored based on findings. Follow-up data assessed changes in body composition and complication rates. Results: Hypertension was the most prevalent BP variation (63.2%), followed by hypotension (26.4%) and intradialytic hypotension (IDH) (8%). Malnutrition affected 24.8% of patients, primarily older males. During follow-up, patients with normal indices of lean tissue (28 to 54), fat tissue (28 to 54) and BMI (28 to 54) increased significantly. The most common dialysis-related complications were cramps (43.2%), itching (28%) and edema (20.8%). Targeted interventions, including nutritional supplementation and BCM-guided fluid management, reduced complications and improved nutritional and hemodynamic parameters. Conclusions: The study highlights the high prevalence of hypertension and malnutrition among hemodialysis patients and underscores the utility of BCM in optimizing patient management. BCM-guided interventions were associated with improved nutritional status and reduced complications, emphasizing the need for individualized care strategies. Further multicenter studies are recommended to validate these findings and expand their applicability.